2016
DOI: 10.1016/j.evalprogplan.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Planning an integrated agriculture and health program and designing its evaluation: Experience from Western Kenya

Abstract: HighlightsComplex, integrated development programs present planning and evaluation challenges and opportunities.Multiple evaluation components are needed to respond to different disciplinary cultures of evidence in cross-sectoral programs.Delineating impact pathways helps visualize cross-sectoral outcomes and guides implementation monitoring.Feedback meetings are critical to build understanding across sectors and problem-solve in real time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…Our results corroborate with previous findings regarding economic benefits of interventions in QPM (Gunaratna, Groote, Nestel, Pixley, & McCabe, ), OFSP (Cole et al, ), biofortified iron beans (Murekezi et al, ), bananas (Shimwela et al, ), crop‐livestock integration (Mottet et al, ), improved livestock breeds (Argent et al, ) and farmer capacity building (Davis et al, ) to sync sowing time with rainfall (Mottet et al, ), investments in sustainable soil and water management (Shikuku et al, ) and greater participation of non‐state actors (Shin et al, ).…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 91%
“…Our results corroborate with previous findings regarding economic benefits of interventions in QPM (Gunaratna, Groote, Nestel, Pixley, & McCabe, ), OFSP (Cole et al, ), biofortified iron beans (Murekezi et al, ), bananas (Shimwela et al, ), crop‐livestock integration (Mottet et al, ), improved livestock breeds (Argent et al, ) and farmer capacity building (Davis et al, ) to sync sowing time with rainfall (Mottet et al, ), investments in sustainable soil and water management (Shikuku et al, ) and greater participation of non‐state actors (Shin et al, ).…”
Section: Conclusion and Policy Recommendationssupporting
confidence: 91%
“…Like ours, other studies have identified breakdowns in the pathway between training and effective application of its contents, including the volume of content to be absorbed, the skills and attributes of trainers, logistical and human challenges to adequate supervision, and the considerable and perhaps unrealistic demands placed on community agents (Kim et al, ; Mbuya, Menon, Habicht, Pelto, & Ruel, ). Such research has documented exposure to the intervention (Avula et al, ; Rajaraman et al, ) as well as gaps in delivery (Mbuya et al, ) and has deepened understanding of the complexities of such multisectoral public health undertakings (Cole et al, ; Harris et al, ). In our study, although master trainers evinced good understanding of the ENA concepts, there was considerable loss through the cascade to OWL/HC and then mothers, which led us to increase the frequency of refresher training and supervision and reinforce communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…The impact pathway and subsequent monitoring and evaluation strategy covered all major areas of inputs, actions, and outcomes including the following: knowledge and attitudes; diet, nutrition, and health; seed systems; production practices; and cross-sectorial (horizontal) integration (5). However, the implementation of Mama SASHA faced several challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Through community and health facility platforms, the project targeted households with PLW with enhanced nutrition education by using inputs in the form of vouchers for OFSP planting materials and enhanced agricultural extension (5). Demographic and Health Survey data available just before program development indicated undernutrition and low coverage with VA supplementation programs as public health concerns for young children and women of reproductive age in Western Kenya (6).…”
Section: Introductionmentioning
confidence: 99%